DIVIDEN POLICY INFLUENCE ON VALUE OF THE FIRM IN INDONESIA : CAPM-based empiric research on Go-public Company in Jakarta Stock Exchange - Wijaya NIM. 281 98 185, Chandra
Abstract: Empiric studies on dividend policy influence on value of the firm by financial experts have concluded varied results. In general some of the study results might be classified into two main groups. The first group suggested that dividend policy has influenced value of the firm, and the second one has not. Basically this research was purposed to answer two fundamental questions. The first one is, "Did dividend policy a company have made influence value of the firm reflected in market?" The second one is, "Which one of dividend theories has proved relevant to Indonesia? To respond to the above research problems researcher has undertaken a literature study on various existing dividend theories. They consisted of a) Dividend Irrelevance Theory by Modigliani and Miller, b) The Bird in The Hand Theory by Gordon and Lintner, and c) Tax Differentiation Theory by Litzenberger and Ramaswamy. Approach used to do empiric examination to prove which was the valid one, researcher have applied theory of Litzenberger and Ramaswamy (1980), Capital Assets Pricing Model (CAPM) by sharpe plus the third variable, dividend yield. Thus, we obtain the following CAPM equation: Ks =KRF + βi(KM -KRF)+ γi(DYi -DM) Using multiplied regression, and then Ks, KM, KRF, DYi and DM have been analyzed. From this multiplied regression analysis we got βi and γi values. If γi was 0, it means (DYi - DM) had no influence on Ks. The result supported Dividend Irrelevance Theory of Modigliani and Miller. If γi positive, it means (DYi - DM) had positive influence on Ks. This result uphelp Tax Differentiation Theory of Litzenberger and Ramaswamy. If γi was negative, it means (DYi - DM) had negative influence on Ks. It shows that investors preferred dividend yield or maintained The Bird in The Hand Theory of Gordon dan Lintner. Research population was all companies listed in Jakarta Stock Exchange (BEJ) as of May 31, 2000 accounted for 282 emitting companies. They were taken using stratified sampling with four criteria: emiting companies should do lisitng prior to January 2000, not under delisting criterion, given audited financial statement, not accepted disclaimer opinion, and paid dividend in cash since 1996. As a result, there were only 100 emitting samples remained. To get reliable study result, time period of this observation was taken from January 1966 to May 2000 based on daily observation timing unit or total 1,087 days of observation. Data processing through SPSS Program Version 10 concluded The Bird in the Hand as Gordon and Lintner proposed has empirically proved seriously vague. It means that dividend policy had positive influence on value of the firm (rejecting Ho and accepting Ha). It is true that dividend coefficient were higher than risk premium coefficient, both in LR-1 Model (0.015050 to 0.007739) and LR-2 Model (0.013420 to 0.007690). It has proved that dividend yield were preferred to capital gain. Based on the findings researcher has recommended that to increase stock prices in Stock Exchange, emitting companies should be accurate in running their dividend policies. They could do this by rising their paid stock prices per dividend due to positive influence on elevated price of stock was relatively weak. In analyzing stock prices, it is better for investors to concentrate on dividend yield and risk premium. Additionally, they need to consider such another factors as developments and changes in social, politic, culture and safety.